Two carboxylesterase genes in Plutella xylostella associated with sex pheromones and plant volatiles degradation. Issue 6 (22nd February 2021) - Wang, Mei‐Mei; Long, Gui‐Jun; Guo, Huan; Liu, Xuan‐Zheng; Wang, Hong; Dewer, Youssef; Li, Zhao‐Qun; Liu, Kun; Zhang, Qiu‐Liang; Ma, Yun‐Feng; He, Peng; He, Ming
Abstract: BACKGROUND: Carboxyl/cholinesterases (CCEs) are thought to play a pivotal role in the degradation of sex pheromones and plant‐derived odorants in insects, but their exact biochemistry and physiological functions remain unclear. RESULTS: In this study, two paralogous antennae‐enriched CCEs from Plutella xylostella (PxylCCE16a and 16c) were identified and functionally characterized. High‐purity protein preparations of active recombinant PxylCCE16a and 16c have been obtained from Sf 9 insect cells by Ni 2+ affinity purification. Our results revealed that the purified recombinant PxylCCE016c is able to degrade two sex pheromone components Z9‐14:Ac and Z11‐16:Ac at 27.64 ± 0.79% and 24.40 ± 3.07%, respectively, while PxylCCE016a presented relatively lower activity. Additionally, a similar difference in activity was measured in plant‐derived odorants. Furthermore, both CCEs displayed obvious preferences for the two sex pheromone components, especially on Z11‐16:Ac ( K m values are in the range 7.82–45.06 μmol L –1 ) which much lower than plant odorants ( K m values are in the range 1290–4030 μmol L –1 ). Furthermore, the activity of the two newly identified CCEs is pH‐dependent. The activity at pH 6.5 is obviously higher than that at pH 5.0. Interestingly, only PxylCCE016c can be inhibited by a common esterase inhibitor triphenyl phosphate (TPP) with LC50 of 1570 ± 520 μmol L –1 . CONCLUSION: PxylCCE16c plays a more essential role in odorant degradation than PxylCCE16a. Moreover, the current study provides novel potential pesticide targets for the notorious moth Plutella xylostella . © 2021 Society of Chemical Industry Abstract : Two paralogous antennal carboxylesterases in diamondback moth play crucial roles in the degradation of ester sex pheromone components and plant‐derived volatiles, which provides potential pesticide targets.